Camellia zhaiana (sect. Longipedicellata), a new species of Theaceae from Guangxi, China - Liu, Zhenwen; Ye, Pinming; Li, Zhihui; Wei, Xiaojuan; Liu, Ende; Zhang, Zhirong; Ma, Jin-Lin; Yang, Shixiong (Phytotaxa, 2020)
Camellia zhaiana is described and illustrated as a new species from Guangxi, China. It is morphologically related to C. longipedicellata, but can be easily distinguished by its pink and puberulent petals as well as its larger thinly leathery leaves. It is accessed to be Critically Endangered (CR) according to the IUCN Red List Categories and Criteria.